Ephesians i. 3-;14 and I Peter I. 3-12 - Coutts, J. (New Testament studies, 1957)
In this paper I wish to maintain that behind the two passages, Eph. i. 3-14 and I Pet. i. 3-12, lie forms of liturgical prayer, similar in structure, though not identical in content. I shall argue that the relation between each passage and the form which lies behind it is the same, namely that what we have is homily based on a form of prayer, and to some extent reproducing its words. Taken by itself, the evidence for the Ephesians passage is, I think, much stronger. It is possible there, with some show of plausibility, to restore, in its main outline, and some of its details, the original form. When taken together, the two passages add strength to each other.